Assessment of potential health risk associated with the use of Cladophora fracta as mulch - Obek, Erdal; Topal, E. Isil Arslan; Topal, Murat (Springer, 2021)
In this study, cadmium, copper, nickel, zinc, chromium, manganese and lead were determined in Cladophora fracta present in Lake Hazar (Turkey). The health risks (non-carcinogenic and carcinogenic) of heavy metals associated with the use of Cladophora fracta as mulch were also determined. Bioconcentration factor (BCF) and metal pollution index (MPI) were calculated. When compared with reference value (1.5 mg/kg for Cr and 200 mg/kg for Mn), the highest accumulation by Cladophora fracta was seen in the month of June as 1442 +/- 7.2% (23.13 mg/kg) for Cr and the lowest accumulation calculated in the month of July as 5 +/- 0.2% (210 mg/kg) for Mn. In our study, the highest MPI value was 13.69 in September. The magnitude of MPI values of heavy metals determined during April to September appeared in the following order September > August > July > June > May > April. The HQ(ing) (hazard quotient due to ingestion) and HQ(inh) (hazard quotient due to inhalation) in all months were chidren > female > male while the order of HQ(der) (hazard quotient due to dermal) was determined as male > female > children. Non-carcinogenic risk (HQ) and Hazard Index (HI) values in terms of ingestion, inhalation and dermal ways were lower than 1. Also, total HI values were < 1. As a result, there was not non-carcinogenic and carcinogenic risks associated with usage of Cladophora fracta as mulch.
Keywords: Accumulation; C. fracta; Metal; Health risk; Mulch